High-reflection electroless refrigeration coating and preparation method thereof

By using high-reflection base materials, fillers and reflectivity enhancers in electrically-free refrigerated coatings, the problem of insufficient reflectivity of existing coatings is solved, and higher reflectivity and thermal radiation capabilities are achieved, improving the refrigeration effect and coating performance.

CN119799079AActive Publication Date: 2025-04-11GUANGDONG MAYDOS BUILDING MATERIALS LTD CO

Patent Information

Application Number
CN202411901390.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-11
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The reflectivity of existing electrically-free refrigeration coatings is insufficient, which makes it unable to effectively reflect sunlight, increase the temperature of the paint surface and reduce the refrigeration effect.

Method used

High-reflection base material and high-reflection filler are used, combined with silver powder, aluminum powder and reflectivity enhancer, and through vacuum stirring and other processes, the reflectivity and thermal radiation capacity of the coating is improved.

Benefits of technology

It significantly improves the reflectivity of the paint, enhances its thermal radiation capacity, improves the refrigeration effect, and improves the durability and construction performance of the paint.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005203999520000071
    Figure BDA0005203999520000071
Patent Text Reader

Abstract

The invention provides a high-reflection electroless refrigeration coating and a preparation method thereof. The high-reflection electroless refrigeration coating is prepared from the following raw materials: 150 to 250 parts of high-reflection base material, 30 to 50 parts of high-reflection filler, 20 to 30 parts of titanium dioxide, 2 to 5 parts of silver powder, 15 to 30 parts of aluminum powder, 50 to 100 parts of acetic ether and 50 to 100 parts of reflectivity enhancer, the high-reflection base material comprises vinylidene fluoride, polyacrylate and zinc oxide, and the weight ratio of the vinylidene fluoride to the polyacrylate to the zinc oxide is (3-5): (2-6): (1-3). The high-reflection electroless refrigeration coating provided by the invention has relatively high reflectivity, excellent heat radiation capability and excellent refrigeration effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, and in particular to a highly reflective non-electrical refrigeration coating and a preparation method thereof. Background Art

[0002] Non-electric cooling paint is a new type of paint that can achieve cooling effect without electricity or refrigerant. This paint uses outer space as the cooling source to effectively radiate the heat on the surface of the object through efficient solar reflection and mid-infrared thermal radiation mechanism, thus achieving a cooling effect below the ambient temperature.

[0003] The reflectivity of conventional non-electric cooling paint on the market is only about 90%, which makes it unable to effectively reflect sunlight, thus increasing the heat absorbed by the paint. This will cause the temperature of the paint surface to rise and the cooling effect to weaken. Therefore, there is an urgent need for a non-electric cooling paint with high reflectivity. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides a highly reflective non-electrical refrigeration coating and a preparation method thereof.

[0005] According to one aspect of the present invention, a highly reflective non-electric refrigeration coating is provided. Calculated by weight, raw materials for preparing the highly reflective non-electric refrigeration coating include: 150 to 250 parts of a highly reflective base material, 30 to 50 parts of a highly reflective filler, 20 to 30 parts of titanium dioxide, 2 to 5 parts of silver powder, 15 to 30 parts of aluminum powder, 50 to 100 parts of ethyl acetate, and 50 to 100 parts of a reflectivity enhancer; the highly reflective base material includes vinylidene fluoride, polyacrylate, and zinc oxide, and the weight ratio of vinylidene fluoride, polyacrylate, and zinc oxide is (3 to 5): (2 to 6): (1 to 3).

[0006] The high-reflection base material used in the present invention is prepared from polyvinylidene fluoride, polyacrylate and zinc oxide. The high-reflection base material has the common advantages of polymers and nanoparticles, and not only has excellent optical and thermal properties, but also has good flexibility and durability, and can improve the reflectivity and thermal radiation capacity of the coating.

[0007] Preferably, the high reflective filler includes nano calcium carbonate, aluminum oxide, and calcium silicate, and the weight ratio of nano calcium carbonate, aluminum oxide, and calcium silicate is (3-5): (2-6): (1-3).

[0008] The invention uses a high-reflection filler prepared from nano calcium carbonate, aluminum oxide and calcium silicate. The high-reflection filler replaces the common filler and can effectively improve the reflectivity of the coating.

[0009] Preferably, calculated by weight, the raw materials used to prepare the reflectivity enhancer include: 15-20 parts of kaolin, 15-20 parts of dolomite, 7-10 parts of calcium carbonate, 7-13 parts of zircon sand, 2-5 parts of barium titanate, 20-30 parts of a first enhancing solvent, and 25-35 parts of a second enhancing solvent.

[0010] Preferably, the first enhanced solvent is prepared from xylene, rosin oil and butanone, and the weight ratio of xylene, rosin oil and butanone is (0.5-1.5): (2-4): (0.5-1.5).

[0011] The first enhancing solvent used in the present invention is prepared from xylene, rosin oil and butanone. The first enhancing solvent is a high-solubility solvent that can fully dissolve the polymer and other solid components in the coating to ensure the stability and construction performance of the coating, thereby better dispersing the pigments and fillers and making them more evenly distributed in the coating, thereby improving the reflectivity of the coating.

[0012] Preferably, the second enhancing solvent is copolymerized from dimethyl sulfoxide and polyethylene glycol, and the weight ratio of dimethyl sulfoxide to polyethylene glycol is (3-5):(2-4).

[0013] The second enhancing solvent used in the present invention is copolymerized by dimethyl sulfoxide and polyethylene glycol. The second enhancing solvent is a low-volatile solvent, which can prolong the drying time of the coating, so that the coating has more sufficient reaction time for leveling and densification, thereby reducing the tiny defects on the coating surface, improving the smoothness and glossiness of the coating, and indirectly improving the reflectivity.

[0014] Preferably, calculated by weight, the raw materials for preparing the highly reflective non-electric refrigeration coating also include: 10 to 15 parts of a dispersant, 5 to 10 parts of a leveling agent, 7 to 9 parts of a thickener, and 2 to 4 parts of a defoaming agent.

[0015] According to another aspect of the present invention, there is provided a method for preparing a highly reflective non-electric refrigeration coating, comprising the following steps:

[0016] S1. The highly reflective base material, the highly reflective filler, titanium dioxide, silver powder, aluminum powder, ethyl acetate, a dispersant, a leveling agent and a defoaming agent are mixed and reacted at a temperature of 70 to 100° C. to obtain a mixture A;

[0017] S2. Preparing a reflectivity enhancer in a grinder; the reflectivity enhancer contains kaolin, dolomite, calcium carbonate, zircon sand, barium titanate, a first enhancing solvent and a second enhancing solvent;

[0018] S3. Put the mixture A and the reflectivity enhancer into a vacuum mixer and stir to obtain a highly reflective non-electrical refrigeration coating.

[0019] Preferably, the reaction stirring speed in step S1 is 200-300 rpm, and the reaction time is 3-5 h.

[0020] Preferably, in step S2, the grinding machine has a mesh precision of 600-700 meshes, a rotation speed of 20-50 rpm, and a grinding time of 7-9 hours.

[0021] Preferably, in step S3, the speed of the vacuum stirrer is 200-300 rpm, and the stirring time is 2-3 hours.

[0022] Preferably, the vacuum degree of the vacuum mixer in step S3 is (-0.08) to (-0.09) MPa.

[0023] Preferably, the weight ratio of mixture A and reflectivity enhancer in step S3 is (5-7):2. DETAILED DESCRIPTION

[0024] The following is a further clear and complete description of the technical features in the technical solution provided by the present invention in conjunction with the specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0025] Example 1

[0026] A highly reflective non-electric refrigeration coating is prepared by the following steps:

[0027] S1. 150 parts by weight of a highly reflective base material, 30 parts by weight of a highly reflective filler, 20 parts by weight of titanium dioxide, 2 parts by weight of silver powder, 15 parts by weight of aluminum powder, 50 parts by weight of ethyl acetate, 10 parts by weight of a dispersant, 5 parts by weight of a leveling agent, 7 parts by weight of a thickener, and 2 parts by weight of a defoaming agent were mixed and reacted at a temperature of 70 to 100° C. to obtain a mixture A;

[0028] S2 prepared in a grinder reflectivity enhancer; reflectivity enhancer containing 15 parts by weight of kaolin, 15 parts by weight of dolomite, 7 parts by weight of calcium carbonate, 7 parts by weight of zircon sand, 2 parts by weight of barium titanate, 20 parts by weight of the first enhancing solvent and 25 parts by weight of the second enhancing solvent;

[0029] S3. Put the mixture A and the reflectivity enhancer into a vacuum mixer and stir to obtain a highly reflective non-electrical refrigeration coating.

[0030] The high reflective base material includes vinylidene fluoride, polyacrylate, and zinc oxide, and the weight ratio of vinylidene fluoride, polyacrylate, and zinc oxide is 3:2:1;

[0031] The high reflective filler includes nano calcium carbonate, aluminum oxide, and calcium silicate, and the weight ratio of nano calcium carbonate, aluminum oxide, and calcium silicate is 3:2:1;

[0032] The first enhanced solvent is prepared from xylene, rosin oil and butanone, and the weight ratio of xylene, rosin oil and butanone is 0.5:2:0.5;

[0033] The second enhancing solvent is copolymerized by dimethyl sulfoxide and polyethylene glycol, and the weight ratio of dimethyl sulfoxide to polyethylene glycol is 3:2;

[0034] Wherein, the reaction stirring speed in step S1 is 200 rpm, and the reaction time is 3 h;

[0035] Among them, in step S2, the grinding machine mesh precision is 600 mesh, the rotation speed is 20rpm, and the grinding time is 7h;

[0036] Wherein, in step S3, the speed of the vacuum mixer is 200 rpm and the stirring time is 2 h;

[0037] Wherein, the vacuum degree of the vacuum condition in step S3 is -0.08MPa;

[0038] Wherein, the weight ratio of mixture A and reflectivity enhancer in step S3 is 5:2.

[0039] Example 2

[0040] A highly reflective non-electric refrigeration coating is prepared by the following steps:

[0041] S1. 200 parts by weight of a highly reflective base material, 40 parts by weight of a highly reflective filler, 25 parts by weight of titanium dioxide, 3 parts by weight of silver powder, 22 parts by weight of aluminum powder, 75 parts by weight of ethyl acetate, 13 parts by weight of a dispersant, 7 parts by weight of a leveling agent, 8 parts by weight of a thickener, and 3 parts by weight of a defoaming agent are mixed and reacted at a temperature of 70 to 100° C. to obtain a mixture A;

[0042] S2. A reflectivity enhancer was prepared in a grinder; the reflectivity enhancer contained 17 parts by weight of kaolin, 17 parts by weight of dolomite, 8 parts by weight of calcium carbonate, 10 parts by weight of zircon sand, 3 parts by weight of barium titanate, 25 parts by weight of a first enhancing solvent and 30 parts by weight of a second enhancing solvent;

[0043] S3. Put the mixture A and the reflectivity enhancer into a vacuum mixer and stir to obtain a highly reflective non-electrical refrigeration coating.

[0044] The high reflective base material includes vinylidene fluoride, polyacrylate, and zinc oxide, and the weight ratio of vinylidene fluoride, polyacrylate, and zinc oxide is 4:4:2;

[0045] The high reflective filler includes nano calcium carbonate, aluminum oxide, and calcium silicate, and the weight ratio of nano calcium carbonate, aluminum oxide, and calcium silicate is 4:4:2;

[0046] The first enhanced solvent is prepared from xylene, rosin oil and butanone, and the weight ratio of xylene, rosin oil and butanone is 1:3:1;

[0047] The second enhancing solvent is copolymerized by dimethyl sulfoxide and polyethylene glycol, and the weight ratio of dimethyl sulfoxide to polyethylene glycol is 4:3;

[0048] Wherein, the reaction stirring speed in step S1 is 250 rpm and the reaction time is 4 h;

[0049] Among them, in step S2, the grinding machine mesh precision is 650 mesh, the rotation speed is 35rpm, and the grinding time is 8h;

[0050] Wherein, in step S3, the speed of the vacuum mixer is 250 rpm, and the stirring time is 2.5 h;

[0051] Wherein, the vacuum degree of the vacuum condition in step S3 is -0.085MPa;

[0052] Wherein, the weight ratio of mixture A and reflectivity enhancer in step S3 is 6:2.

[0053] Example 3

[0054] A highly reflective non-electric refrigeration coating is prepared by the following steps:

[0055] S1. 250 parts by weight of a highly reflective base material, 50 parts by weight of a highly reflective filler, 30 parts by weight of titanium dioxide, 5 parts by weight of silver powder, 30 parts by weight of aluminum powder, 100 parts by weight of ethyl acetate, 15 parts by weight of a dispersant, 10 parts by weight of a leveling agent, 9 parts by weight of a thickener, and 4 parts by weight of a defoaming agent are mixed and reacted at a temperature of 70 to 100° C. to obtain a mixture A;

[0056] S2. A reflectivity enhancer was prepared in a grinder; the reflectivity enhancer contained 20 parts by weight of kaolin, 20 parts by weight of dolomite, 10 parts by weight of calcium carbonate, 13 parts by weight of zircon sand, 5 parts by weight of barium titanate, 30 parts by weight of a first enhancing solvent and 35 parts by weight of a second enhancing solvent;

[0057] S3. Put the mixture A and the reflectivity enhancer into a vacuum mixer and stir to obtain a highly reflective non-electrical refrigeration coating.

[0058] The high reflective base material includes vinylidene fluoride, polyacrylate, and zinc oxide, and the weight ratio of vinylidene fluoride, polyacrylate, and zinc oxide is 5:6:3;

[0059] The high reflective filler includes nano calcium carbonate, aluminum oxide, and calcium silicate, and the weight ratio of nano calcium carbonate, aluminum oxide, and calcium silicate is 5:6:3;

[0060] The first enhanced solvent is prepared from xylene, rosin oil and butanone, and the weight ratio of xylene, rosin oil and butanone is 1.5:4:1.5;

[0061] The second enhancing solvent is copolymerized by dimethyl sulfoxide and polyethylene glycol, and the weight ratio of dimethyl sulfoxide to polyethylene glycol is 5:4;

[0062] Wherein, the reaction stirring speed in step S1 is 300 rpm and the reaction time is 5 h;

[0063] Among them, in step S2, the grinding machine mesh precision is 700 mesh, the rotation speed is 50rpm, and the grinding time is 9h;

[0064] Wherein, in step S3, the speed of the vacuum mixer is 300 rpm and the stirring time is 3 h;

[0065] Wherein, the vacuum degree of the vacuum condition in step S3 is -0.09MPa;

[0066] Wherein, the weight ratio of mixture A and reflectivity enhancer in step S3 is 7:2.

[0067] Example 4

[0068] This embodiment provides a highly reflective non-electric refrigeration coating. Compared with the embodiment 1, the difference in structure is that the highly reflective base material is prepared only from polyacrylate and zinc oxide, and the weight ratio of polyacrylate to zinc oxide is 2:1. Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0069] Example 5

[0070] This embodiment provides a highly reflective non-electric refrigeration coating, and compared with the embodiment 1, the difference in structure is that the highly reflective filler is only prepared from nano calcium carbonate. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0071] Example 6

[0072] This embodiment provides a highly reflective non-electric refrigeration coating, and compared with the embodiment 1, the difference in structure is that the first enhancement solvent is prepared from xylene only. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0073] Example 7

[0074] This embodiment provides a highly reflective non-electric refrigeration coating, and compared with the embodiment 1, the difference in structure is that the second enhancement solvent is prepared from only dimethyl sulfoxide. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0075] Test Case

[0076] 1. Participants

[0077] In this test example, the highly reflective non-electric refrigeration coatings prepared in Examples 1 to 7 and common non-electric refrigeration coatings on the market were used as test objects to conduct relevant performance tests.

[0078] 2. Test content

[0079] In this test example, the surfaces of the highly reflective non-electric cooling coatings prepared in Examples 1 to 7 and the common non-electric cooling coatings on the market were used as coating surfaces, and the experiment was conducted in an outdoor environment, and the three coatings were separated by 1.2-1.5 m.

[0080] 3. Test results

[0081] Table 1 Related performance test results of high reflective non-electric refrigeration coating

[0082]

[0083]

[0084] The relevant performance test results of the highly reflective non-electric refrigeration coatings provided in Examples 1 to 7 and the common non-electric refrigeration coatings on the market are shown in Table 1.

[0085] From the perspective of reflectivity, the reflectivity of Examples 1 to 3 is relatively high, maintained between 96.3% and 97.6%. This is mainly due to the fact that they use a complete high-reflectivity base material formula (vinylidene fluoride, polyacrylate, zinc oxide) and a high-reflectivity filler formula (nano-calcium carbonate, aluminum oxide, calcium silicate), as well as an optimized reflectivity enhancer preparation. The reflectivity of Example 4 drops to 94.1%, which may be due to the lack of vinylidene fluoride in the high-reflectivity base material, which affects the optical properties of the coating. The reflectivity of Example 5 is 95.3%, which is still higher than the common coatings on the market, but is lower than that of Examples 1 to 3. This may be because the high-reflectivity filler only uses nano-calcium carbonate, lacking the synergistic effect of aluminum oxide and calcium silicate. Example 6 and Example 7: The reflectivity drops to 93.2% and 93.5%, respectively. This may be because the formula of the first enhancement solvent or the second enhancement solvent is incomplete, which affects the dispersion and uniformity of the coating, thereby reducing the reflectivity. The common non-electric refrigeration coatings on the market have the lowest reflectivity, which is only 90.2%, indicating that the coating of the present invention has obvious advantages in terms of reflectivity.

[0086] From the perspective of volume solids, the volume solids of all examples are relatively high, ranging from 57.8% to 62.3%, indicating that the active ingredient content in the coating is high and the coating film quality is good. The volume solids of the common non-electric refrigeration coating on the market are also relatively high (62.1%), but the reflectivity is relatively low, indicating that its active ingredients may not be fully exerted.

[0087] From the 500-hour weathering test, the coatings of all the examples performed well in the 500-hour weathering test, without cracks or peeling. This shows that the coatings have good durability and stability. The common non-electric refrigeration coatings on the market have no cracks or peeling in the 300-hour weathering test, but their weathering resistance is poorer than that of the coatings of the examples.

[0088] From the perspective of the surface temperature after 5 hours of exposure to the sun, the surface temperature of Examples 1 to 3 is relatively low after 5 hours of exposure to the sun, maintained between 35.7°C and 36.8°C. This shows that these coatings have high reflective heat insulation performance and can effectively reduce the absorption and conduction of solar radiation. The surface temperature of Examples 4 to 7 rose slightly after 5 hours of exposure to the sun, but was still lower than the common non-electric refrigeration coatings on the market (46.2°C). This shows that the reflective heat insulation performance of the coating of the present invention is better than that of the common coatings on the market, but there are certain differences between different formulations.

[0089] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.

Claims

1. A highly reflective non-electric refrigeration coating, characterized in that: Calculated by weight, the raw materials for preparing the highly reflective non-electric refrigeration coating include: 150-250 parts of a highly reflective base material, 30-50 parts of a highly reflective filler, 20-30 parts of titanium dioxide, 2-5 parts of silver powder, 15-30 parts of aluminum powder, 50-100 parts of ethyl acetate, and 50-100 parts of a reflectivity enhancer; The high-reflection base material includes vinylidene fluoride, polyacrylate, and zinc oxide, and the weight ratio of the vinylidene fluoride, the polyacrylate, and the zinc oxide is (3-5): (2-6): (1-3).

2. The highly reflective non-electric refrigeration coating according to claim 1, characterized in that: The high-reflection filler includes nano-calcium carbonate, aluminum oxide, and calcium silicate, and the weight ratio of the nano-calcium carbonate, the aluminum oxide, and the calcium silicate is (3-5): (2-6): (1-3).

3. The highly reflective non-electric refrigeration coating according to claim 1, characterized in that: Calculated by weight, the raw materials used to prepare the reflectivity enhancer include: 15 to 20 parts of kaolin, 15 to 20 parts of dolomite, 7 to 10 parts of calcium carbonate, 7 to 13 parts of zircon sand, 2 to 5 parts of barium titanate, 20 to 30 parts of a first enhancing solvent, and 25 to 35 parts of a second enhancing solvent.

4. The highly reflective non-electric refrigeration coating according to claim 3, characterized in that: The first enhanced solvent is prepared from xylene, rosin oil and butanone, and the weight ratio of the xylene, the rosin oil and the butanone is (0.5-1.5): (2-4): (0.5-1.5).

5. The highly reflective non-electric refrigeration coating according to claim 3, characterized in that: The second enhancing solvent is copolymerized by dimethyl sulfoxide and polyethylene glycol, and the weight ratio of the dimethyl sulfoxide to the polyethylene glycol is (3-5): (2-4).

6. The highly reflective non-electric refrigeration coating according to claim 1, characterized in that: Calculated by weight, the raw materials for preparing the highly reflective non-electric refrigeration coating also include: 10 to 15 parts of a dispersant, 5 to 10 parts of a leveling agent, 7 to 9 parts of a thickener, and 2 to 4 parts of a defoaming agent.

7. A method for preparing the highly reflective non-electric refrigeration coating as claimed in claims 1 to 6, characterized in that: The following steps are involved: S1. Mixing the high-reflective base material, the high-reflective filler, the titanium dioxide, the silver powder, the aluminum powder, the ethyl acetate, the dispersant, the leveling agent and the defoamer at a temperature of 70 to 100° C. to obtain a mixture A; S2. Preparing a reflectivity enhancer in a grinder; the reflectivity enhancer containing the kaolin, the dolomite, the calcium carbonate, the zircon sand, the barium titanate, the first enhancing solvent and the second enhancing solvent; S3. Put the mixture A and the reflectivity enhancer into a vacuum mixer and stir to obtain a highly reflective non-electric refrigeration coating.

8. The preparation method according to claim 7, characterized in that: The vacuum degree of the vacuum condition in step S3 is (-0.08) to (-0.09) MPa.

9. The preparation method according to claim 7, characterized in that: In step S3, the weight ratio of the mixture A to the reflectivity enhancer is (5-7):2.

Citation Information

Patent Citations

  • Aqueous compositions based on polychloroprene

    CA2527630A1

Cited By

  • Non-electric refrigeration composite coating with press-clamping effect and preparation method of non-electric refrigeration composite coating

    CN121517965A